Occlusion: a fundamental concept in dentistry - Nelson Cortés-Castaño (Universidad de Antioquia, 2009)
The word occlusion has been employed in dentistry to describe the teeth alignment, their place in the dental arch and the contacts between their masticatory surfaces. From all the occlusal classifications proposed in the past, only one, described by Angle is used today from which the words normal occlusion and malocclusion have been used routinely. This paper analyzed the difficulties of the dental profession to obtain a conceptual approach to its objects of knowledge, part of it due to its adscription to the positive speech of science, but also due to the inadequacy of the teaching strategies in several educational institutions, centered in an image as the only method of learning that has placed the students in incapacity to conceive the occlusion free from the material concept of object-thing. This text intents to place the 'occlusal concept' in the scope of the dental profession as an elaborate effect of thinking that, although it may take origin in the organic of the teeth, must go through its representation to emerge as a concept, perhaps the only one that belongs to dentistry.